Checkpoint modulation - A new way to direct the immune system against renal cell carcinoma - Bedke, Jens; Kruck, Stephan; Gakis, Georgios; Stenzl, Arnulf; Goebell, Peter (Human Vaccines and Immunotherapeutics, 2015)
The introduction of targeted therapies like the tyrosine kinase (TKI) and mammalian target of rapamycin (mTOR) inhibitors has improved patients' survival in general. Nevertheless the prognosis remains limited. Therapies with a new mode of action are urgently warranted, especially those who would provoke long-term responders or long-lasting complete remissions as observed with unspecific immunotherapy with the cytokines interleukin-2 and interferon-?. In the recent years a deeper understanding of the underlying immunology of T cell activation led to the development of checkpoint inhibitors, which are mainly monocloncal antibodies and which enhances the presence of the co-stimulatory signals needed for T cell activation or priming. This review discusses the clinical data and ongoing studies available for the inhibition of the PD-1 (CD279) and CTLA-4 (CD152) axis in mRCC. In addition, potential future immunological targets are discussed. This approach of T-cell activation or re-activation by immunological checkpoint inhibition holds the inherent promise to directly affect the tumor cell and thereby to potentially cure a subset of patients with mRCC.
EVALuna2:16350